Salivary menopausal markers and oral health status - A hidden hook up - B Soundarya; F Massillamani; S Kailasam; G Jayashree; N Narmadha; N Sornaa (Wolters Kluwer Medknow Publications, 2022)
Aim and Objectives: The aim of our study was to evaluate salivary estradiol and salivary calcium in postmenopausal women with varying degrees of oral dryness. The primary objective was to establish the interrelationship between salivary parameters and oral health status among menopausal women and compare the same with premenopausal women and normal controls. Materials and Methods: The study included 60 women Group I consisted of healthy menstruating women between 25 and 34 years of age. In Group II premenopausal women between 35 and 45 years of age were present and Group III consisted of menopausal women between 45 and 60 years of age. Unstimulated saliva was collected from the participants and estradiol analysis was done using ELISA method and calcium analysis was done using Arsenazo III reaction using colorimetric method. The oral health status in these patients was determined by using xerostomia score, Russell's periodontal score, and oral hygiene index. The values obtained were subjected to statistical analysis and the results were derived. Results: On oral examination, most of them had poor oral hygiene, periodontal disease, and moderate to severe levels of xerostomia. Salivary estradiol levels were low and salivary calcium levels were high among postmenopausal women and as salivary estradiol levels decreased there was an increase in xerostomia scores and salivary calcium. And also as salivary calcium levels increased the periodontal disease scores increased. All parameters were within normal limits among healthy menstruating women. Conclusion: Saliva can be a preferred medium and an emerging alternative for serum to estimate estradiol and calcium levels. As a dentist, we have to educate them about the oral changes they will experience during menopause and emphasize its strong association between low estradiol levels. Oral hygiene instructions should be given for the maintenance of healthy periodontium. Menopausal women who experience severe postmenopausal symptoms can be identified and the dentist and gynecologist can work hand in hand to treat the symptoms of these women.